mTOR/p70S6K Signal transduction pathway contributes to osteosarcoma progression and patients’ prognosis - Zhou, Quan; Deng, Zhansheng; Zhu, Yong; Long, Haitao; Zhang, Shaoxian; Zhao, Jiali (Medical oncology (Northwood, London, England), 2010)
The mTOR/p70S6K signal transduction pathway plays a key role in the regulation of cancer cells’ survival and proliferation. However, its roles in osteosarcoma, which is one of the most rapidly growing sarcomas, remain unknown. This study investigated for the first time the correlation between the mTOR/p70S6K signal transduction pathway in human osteosarcoma and patients’ prognosis. The expression patterns of mTOR and p70S6K in paraffin-embedded specimens gathered from 65 patients with primary osteosarcoma were detected by the method of immunohistochemistry using antibodies against mTOR and p70S6K. Kaplan–Meier survival and Cox regression analyses were performed to evaluate the prognosis of patients. Immunostaining revealed that the mTOR/p70S6K signal transduction pathway is activated in human osteosarcoma. Additionally, positive expression of mTOR and p70S6K proteins was significantly correlated with surgical stage, metastasis pattern and percentage of dead cells of osteosarcoma. Moreover, in univariate analysis, surgical stage, metastasis pattern and percentage of dead cells, mTOR and p70S6K expression showed significant influence on overall survival (OS) and disease-free survival (DFS). In multivariate analysis, surgical stage (IIA vs. IIB/III), metastasis pattern (without vs. with), percentage of dead cells (≥90 vs. <90%), mTOR expression pattern (negative vs. positive) and p70S6K expression pattern (negative vs. positive) were significant for DFS and OS. Our results demonstrate the correlation of mTOR and p70S6K expression patterns with the oncological progression of osteosarcoma patients, suggesting the prognostic significance of the mTOR/p70S6K signal transduction pathway in osteosarcoma patients, which may lay a foundation for making further investigations on the mTOR/p70S6K signal transduction pathway as a potential target for osteosarcoma therapy.